On the Presence of Five Species of Naupactini (Coleoptera: Curculionidae) Damaging Soybean in Brazil - Lanteri, Analía Alicia (2013)
We report five broad-nosed weevils of the tribe Naupactini, Naupactus leucoloma Boheman, Naupactus minor (Buchanan), Naupactus peregrinus (Buchanan), Naupactus tremolerasi Hustache and Pantomorus viridisquamosus (Boheman) (Coleoptera: Curculionidae) damaging soybean plants in the state of Rio Grande do Sul, Brazil. Some of these species are recorded for the first time in Brazil, and they all belong to species groups naturally distributed in the prairies of southern Brazil, Uruguay, Central Argentina and Paraguay. Three of them have been introduced, established and expanded in other countries outside South America. The five species in conjunction with other native species of Naupactini could cause severe damages to soybean crops if the root-feeding larvae attack young growing plants.